2007
DOI: 10.1143/jjap.46.7846
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy in Fe3Si/FeSi2 Superlattices Prepared by Facing Target Direct-Current Sputtering at Room Tempertaure

Abstract: Fe3Si/FeSi2 superlattices were prepared on Si(111) at two deposition rates by facing target direct-current sputtering. For the deposition rates of 2.0 nm/min for Fe3Si and 1.3 nm/min for FeSi2, the Fe3Si layers were nonoriented. On the other hand, for half-deposition rates, the Fe3Si layers were epitaxially grown not only on Si(111) but also up to the top layer across the FeSi2 layers. The antiferromagnetic interlayer coupling between the Fe3Si layers was induced in the epitaxial superlattices, whereas it disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 8 publications
10
18
0
Order By: Relevance
“…This combination has the following specifics: (i) since the electrical conductivity of FeSi 2 spacer layers is an order of magnitude smaller than that of Fe 3 Si layers, a magnetoresistance effect in current-perpendicular-to-plane (CPP) geometry is expected to be detectable; (ii) the epitaxial growth of Fe 3 Si layers on Si(111) substrates is successively kept up to the top Fe 3 Si layer across FeSi 2 spacer layers, which is beneficial to the coherent transportation of spin-polarized electrons; (iii) a strong antiferromagnetic (AF) interlayer coupling can be induced among the ferromagnetic Fe 3 Si layers in spite of the saturation magnetization of Fe 3 Si being one-half of that of Fe; (iv) Fe 3 Si is feasible for a practical use since it has a high Curie temperature of 840 K; (v) d-electrons contribute to the electrical conduction in both layers. Thus far, we have confirmed that B2-type Fe 3 Si layers are epitaxially grown not only on a Si(111) substrate but also up to the top layer across NCFeSi 2 layers and ferromagnetic (F)/AF interlayer couplings are induced by controlling the thickness of NC-FeSi 2 layers [29][30][31][32][33].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…This combination has the following specifics: (i) since the electrical conductivity of FeSi 2 spacer layers is an order of magnitude smaller than that of Fe 3 Si layers, a magnetoresistance effect in current-perpendicular-to-plane (CPP) geometry is expected to be detectable; (ii) the epitaxial growth of Fe 3 Si layers on Si(111) substrates is successively kept up to the top Fe 3 Si layer across FeSi 2 spacer layers, which is beneficial to the coherent transportation of spin-polarized electrons; (iii) a strong antiferromagnetic (AF) interlayer coupling can be induced among the ferromagnetic Fe 3 Si layers in spite of the saturation magnetization of Fe 3 Si being one-half of that of Fe; (iv) Fe 3 Si is feasible for a practical use since it has a high Curie temperature of 840 K; (v) d-electrons contribute to the electrical conduction in both layers. Thus far, we have confirmed that B2-type Fe 3 Si layers are epitaxially grown not only on a Si(111) substrate but also up to the top layer across NCFeSi 2 layers and ferromagnetic (F)/AF interlayer couplings are induced by controlling the thickness of NC-FeSi 2 layers [29][30][31][32][33].…”
Section: Introductionsupporting
confidence: 57%
“…It was confirmed that oriented crystallites were also ordered in-plane to the Si(111) substrate. In our previous study employing transmission electron microscopy, we confirmed that B2-type Fe 3 Si layers are epitaxially grown from the first layer on Si(111) up to the top layer across the FeSi 2 layer with the same orientation relationship as the first layer for structurally similar films [30]. From these results, the Fe 3 Si layers might be partially epitaxially grown from the first layer on Si(111) up to the top layer across the NC-FeSi 2 layers with the same orientation relationship as the first layer.…”
Section: Introductionsupporting
confidence: 56%
“…We have studied spintronics based on a Fe-Si system comprising ferromagnetic Fe3Si and semiconducting FeSi2 thus far [15,16,17,18,19,20,21,22,23,24,25,26]. The combination of Fe3Si and FeSi2 has the following merits [15,16,17,27,28]: (i) the spin injection efficiency might be higher than that in TMR junctions, because the mismatch of the electrical conductivities is less than an order of magnitude, and d electrons contribute to electrical conduction in both layers, (ii) Fe3Si can be epitaxially grown on Si(111) substrates even at room substrate temperature, which is beneficial to the coherent transportation of spin-polarized electrons, and (iii) Fe3Si is feasible for a practical use since it has a high Curie temperature of 840 K and a large saturation magnetization which is half of that of Fe. Additionally, FeSi2 has a large optical absorption coefficient, which is two orders of magnitude larger than that of Si at 1.2 eV.…”
Section: Introductionmentioning
confidence: 99%
“…21,23) For the induction of AF interlayer coupling, the epitaxial growth of Fe 3 Si is indispensable. 22) The trilayered film used in this study has a top Fe 3 Si layer wherein epitaxial and nonepitaxial Fe 3 Si crystallites coexist. The in-plane magnetizations might be prevented by the nonepitaxial Fe 3 Si crystallites from being aligned in an antiparallel manner.…”
Section: Resultsmentioning
confidence: 99%